Heavy metals assessment in selected leafy vegetables from Selangor, Malaysia. - Sian, Nee See; Pak Dek, Mohd Sabri; Sanny, Maimunah; Shukri, Radhiah; Ramli, Nurul Shazini (Universiti Putra Malaysia, 2025)
Leafy vegetables may contain heavy metals that possess negative impacts on human health. However, no structured monitoring has been available so far in terms of the heavy metal content of vegetables sold in markets across the country. Thus, the present study aimed to investigate heavy metals concentration [aluminium (Al), cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe) and lead (Pb)] in selected leafy vegetables (Brassica oleracea subsp. capitata L., Brassica juncea Czern., Spinacia oleracea L., and Brassica rapa var. chinensis) from Selangor wholesale wet markets using inductively coupled plasma–optical emission spectrometry. Potential health risks linked to their consumption were assessed by estimating daily intake of toxic metals (EDI) and calculating both cancer and non-cancer risks, including hazard index and target hazard quotient (THQ). Results showed that the average concentrations of Al and Fe in vegetable samples were within the permissible limits, with the greatest amount of Al found in spinach (41.37 mg/kg). The mean levels of Fe in cabbage, mustard, spinach, and pak choi were 6.30 ± 5.78, 4.12 ± 1.84, 13.59 ± 4.73, and 4.14 ± 0.31 mg/kg, respectively. However, Cd, Cr, Cu, and Pb were undetected in all samples. THQ values derived from the EDI of heavy metals were discovered to be less than one, suggesting a low likelihood of adverse health effects. In conclusion, although leafy vegetables present negligible health risks, consumers should vary their vegetable intake to prevent long-term health effects.